Penggunaan Bungkil Inti Sawit dan Enzim Mannanase dalam Ransum terhadap Performa Produksi Telur Puyuh (Coturnix coturnix japonica) - Noferdiman Noferdiman; Sestilawarti Sestilawarti; Zubaidah Zubaidah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2019)
Noferdiman et al, 2019. The use of palm kernel meal and mannanase enzyme in diets on the production performance of quails (Coturnix coturnix japonica) . JLSO 8(1):11-19.The objective of the study was to investigate the effect of the levels of palm kernel meal and mannanase enzyme in diets to get the best performance of quails. It was used the 180 female quails in treatment combination using the completely randomized design in factorial arrangement of 2 x 3 with 3 replications. Each unit study consisted ofÂ  10 quails. The treatment consisted of 2 levels of mannanase enzyme, i.e. 0.00, 0.10 % and 3 levels of palm kernel meal additions, i.e. 0, 10 and 20 %. The results of the study showed that the use of mannanase enzyme and palm kernel meal and their interaction were no significant (P>0.05) affected feed consumption, eggs production, feed conversion, egg weight, egg shell thickness, and haugh unit (HU). The use of mannanase enzyme highly significant (P<0.01) affected on eggs production and feed conversion however there were no interaction between the treatments. It was concluded that the addition of 0.10 % of mannanase enzyme in diets consisting 20% palm kernel meal can improve the performance egg production of quails.